Health professionals’ readiness to implement electronic medical recording system and associated factors in public general hospitals of Sidama region, Ethiopia - Kibruyisfaw Weldeab Abore; Alemu Tamiso Debiso; Betelhem Eshetu Birhanu; Bezahegn Zerihun Bua; Keneni Gutema Negeri (PLoS ONE, 2022)
Background Electronic medical recording system is one of the information technologies that has a proven benefit to improve the quality of health service. Readiness assessment is one of the recommended steps to be taken prior to implementing electronic medical recording system to reduce the probability of failure. Objective To determine the level of health professional readiness to implement Electronic medical recording system and associated factors in public general hospitals of Sidama region, 2022. Methodology A cross-sectional study design complemented with qualitative study was employed at three public general hospitals in Sidama region on a sample of 306 participants. A pretested self-administered questionnaire was used to collect quantitative data and in-depth interview was used for the qualitative study. Bivariate and multivariate Binary logistics regression was performed to determine predictors of readiness at α = 0.05, using an odds ratio and 95% confidence interval. Thematic analysis was done for qualitative data collected through in-depth interview. Result The overall readiness for health professionals was 36.5%. Of the study participants, 201 (73.4%) were computer literate, 176(64.23%) had good knowledge, and 204 (74.45%) had favorable attitude towards EMR. Only 31 participants had previous training (11.3%), while 64 (23%) had previous experience. EMR knowledge (AOR = 3.332; 95%CI: (1.662, 6.682)) and attitude towards electronic medical recording (AOR = 2.432; 95%CI: (1.146, 5.159)) were statistically significant predictors of readiness to implement electronic medical recording. Qualitative analysis has revealed lack of training, ease of use concerns, information security concerns, and perceived inadequacy of infrastructures including internet connectivity and electricity as common barriers for health professional readiness to implement EMR. Conclusion Health professionals’ readiness in this study was low. Capacity building efforts to increase the awareness and skills of health professionals should be done before implementing the system.